GAYA HIDUP REMAJA DI ERA CYBER - Rosdiana A Bakar (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
Lifestyle actually reflects the class consciousness of certain groups of people including adolescents, in the form of a class ideology. In other words, lifestyle is actually a disclosure of social and cultural meaning. In this case, the visual style is an inseparable joy of lifestyle. It is said that in the era of information globalization where adolescents become the most promising market targets, the visual style plays a major role in shaping their lifestyle. Lifestyle becomes' everything 'and' everything is lifestyle, even style is more important than 'morality'. Cyber, known as the internet age, is an information space and 'virtual' interaction that real body presence is not considered important because the body is not able to access the transcendental or metaphysical world, but it can be done inside the cyber, because the computer networks that make up the cyber basic structure, how to grow, how to adapt and how to send messages that are very similar to how the brain works. It is a seamless global communication and information network through computers around the world. Since adolescence as a 'netters majority' arises our concerns, because it is found that freedom, being a vehicle for cyber-violence, the absence of identity as a vehicle for cyber-porn, the power to control as a vehicle for cyber-crime, the absence of law rides for cyber-anarchy.Keywords: Lifestyle, Teenagers, Cyber